Digenean parasites of the marine gastropods Littorina littorea and Gibbula umbilicalis in the Northern Portuguese Atlantic coast, with a review of digeneans infecting the two gastropod genera - Costa, Graça (2016)
Objective: To study the digenean parasites of the prosobranch gastropods, Littorina littorea (L. littorea) and Gibbula umbilicalis (G. umbilicalis) from rocky shores of the Northern Atlantic coast of Portugal. Methods: A total of 413 L. littorea and 2603 G. umbilicalis were collected from rocky shores, at Aveiro estuary, Aguda Beach, and Foz Beach at Porto (Northern Atlantic coast of Portugal) from January to July 2014 and February 2014 to January 2015, respectively. Gonads and digestive glands of the gastropods were examined under light microscopy for the presence of digeneans. Infected gonads of L. littorea were prepared for histological observation, whereas digeneans found in G. umbilicalis were studied and identified with the aid of light and scanning electron microscopy. Results: Two species of digeneans were found infecting the digestive gland and gonads of G. umbilicalis, namely, Cainocreadium labracis and Lecithochirium furcolabiatum with a combined prevalence of 3%. Histological observations of gonads of L. littorea revealed the infection with digeneans, with considerable replacement of gonadal tissues. These digeneans were not identified to species level. The prevalence of digeneans in this snail host was 0.7%. Conclusions: The present study adds G. umbilicalis as another first intermediate host for Cainocreadium labracis and extends its geographical range to the Portuguese Atlantic coast. Cercariae of Lecithochirium furcolabiatum were previously reported from G. umbilicalis. A literature review of digeneans occurring in the gastropod genera Gibbula and Littorina is given.